2019
DOI: 10.3390/nu11020225
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Nitric Oxide is Involved in the Blood Pressure Lowering Effect of the Peptide AVFQHNCQE in Spontaneously Hypertensive Rats

Abstract: AVFQHNCQE is an antihypertensive nonapeptide obtained from a chicken foot protein hydrolysate. The present study aims to investigate the mechanisms involved in its blood pressure (BP)-lowering effect. Male (17–20 weeks old) spontaneously hypertensive rats (SHR) were used in this study. Rats were divided into two groups and orally administered water or 10 mg/kg body weight (bw) AVFQHNCQE. One hour post-administration, animals of both groups were intra-peritoneally treated with 1 mL of saline or with 1 mL of sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…In this sense, it has been demonstrated that the hydrolysis of chicken foot proteins is a good strategy for the obtaining of bioactive peptides able to reduce BP [ 22 , 24 ]. The NO-mediated antihypertensive effect of the peptide AVFQHNCQE (10 mg/kg bw), identified initially in the chicken foot hydrolysate Hpp11, has been previously demonstrated in SHR [ 22 , 23 ]. Nevertheless, it is unknown if this peptide sequence is susceptible to GI digestion, resulting in new peptide fragments which might be the responsibility of AVFQHNCQE bioactivity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, it has been demonstrated that the hydrolysis of chicken foot proteins is a good strategy for the obtaining of bioactive peptides able to reduce BP [ 22 , 24 ]. The NO-mediated antihypertensive effect of the peptide AVFQHNCQE (10 mg/kg bw), identified initially in the chicken foot hydrolysate Hpp11, has been previously demonstrated in SHR [ 22 , 23 ]. Nevertheless, it is unknown if this peptide sequence is susceptible to GI digestion, resulting in new peptide fragments which might be the responsibility of AVFQHNCQE bioactivity.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of action proposed driven by the stimulation of these opioid receptors is the subsequent NO release causing vasodilation [ 30 , 31 , 32 , 33 ]. Therefore, considering that AVFQHNCQE was not absorbed and its antihypertensive effect was mediated by NO [ 23 ], it was investigated the participation of opioid receptors in its effect on blood pressure. Thus, the antihypertensive properties of AVFQHNCQE were studied in presence of Naloxone, which is an opioid receptor antagonist [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-fructose corn syrup (HFCS) is the main source of added sweeteners in sweetened beverages. A high intake of HFCS causes an increase in BP and thus involves an increase in uric acid production which, in turn, results in a lowering of nitric oxide in the body [43,44]. Other hypotheses behind high SSB intake being implicated in hypertension involve decreased sodium excretion, activation of the sympathetic nervous system [45,46], or an increased sodium concentration in the body through increased gut absorption [47].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these vegetable compounds, this issue includes novel findings regarding the implication of bioactive peptides, amino acids, and fatty acids in different metabolic outcomes. Mas-Capdevila et al raise interesting hypotheses about how the resistance of peptides to gastric digestion may modulate their antihypertensive effect [11], adding a novel approach to previous work about this topic [12,13]. At this point, factors such as bioavailability, synergistic effects between these compounds, or their interaction with other food components, are essential to deepening the knowledge of bioactive compounds on health [4].…”
mentioning
confidence: 99%